A new anthropology of Islam - Bowen, John R. (John Richard), 1951- (Cambridge ; New York : Cambridge University Press, 2012)
"In this powerful but accessible new study John Bowen draws on a full range of work in social anthropology to present Islam in ways that emphasise its constitutive practices, from praying and learning to judging and political organising. Starting at the heart of Islam - revelation and learning in Arabic lands - Bowen shows how Muslims have adapted Islamic texts and traditions to ideas and conditions in the societies in which they live. Returning to key case studies in Indonesia, Africa, Pakistan and Western Europe to explore each major domain of Islamic religious and social life, Bowen also considers the theoretical advances in social anthropology that have come out of the study of Islam. A New Anthropology of Islam is essential reading for all those interested in the study of Islam and for those following new developments in the discipline of anthropology"--
Machine generated contents note: 1. How to think about religions - Islam, for example; 2. Learning; 3. Perfecting piety through worship; 4. Reshaping sacrifice; 5. Healing and praying; 6. Pious organizing; 7. Judging; 8. Migrating and adapting; 9. Mobilizing.
Includes bibliographical references (pages 204-213) and index.
Includes bibliographical references (pages 204-213) and index.
Keywords: Islamic sociology; Anthropology of religion -- Islamic countries